2022
DOI: 10.3390/electronics11213482
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Cooperative Relay NOMA with Large Antenna Transmitters

Abstract: The potential of the Non-Orthogonal Multiple Access (NOMA) approach for wireless communications in the fifth generation (5G) and beyond can not be underestimated. This is because users with favorable channel conditions can serve as relays to improve system performance by employing Successive Interference Cancellation (SIC). Lately, the combination of NOMA and the cooperative relay has attracted the interest of researchers. The analysis of cooperative relay NOMA (CR-NOMA) with a massive multiple-input multiple-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 116 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…However, it is noteworthy that at 𝜆∕4 and 𝜆∕8, the conventional system had a higher average achievable rate and a lower outage probability across all SNR values. In comparing the two coding schemes considered, it can be found that the DF achieved The proposed work and Reference [29] are the only studies that utilise high-frequency transmission. All other references employ low-frequency transmission.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
See 4 more Smart Citations
“…However, it is noteworthy that at 𝜆∕4 and 𝜆∕8, the conventional system had a higher average achievable rate and a lower outage probability across all SNR values. In comparing the two coding schemes considered, it can be found that the DF achieved The proposed work and Reference [29] are the only studies that utilise high-frequency transmission. All other references employ low-frequency transmission.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
“…The authors in [28] developed a conceptual approach for a NOMA-based relaying system and then investigated its performance over Rician fading channels. Recently, the geometric-based stochastic channel model (GBSM) with massive MIMO antenna configuration has attracted considerable attention due to its ability to accurately present the physical characteristics of a communication channel [29,30]. The combination of GBSM, massive MIMO, and CR-NOMA provides a thorough knowledge of system performance based on signal propagation under realistic channel and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations